Тhe methodics of the forming in students literary competence (Pedagogy of Higher and Secondary Education, 2012)
Romanishina N.V. Тhe methodics of the forming in students literary competence.The author of the article offers methodological recommendations, how through the practice of writing short prose works to find and develop in future teachers of literature literary makings, the ability to search for the individual nuances of artistic realization, overcoming destructive automatism, blind and spontaneous imitation of the style of the writer-professional.
Keywords: literary competence; textforming skills; creative thinking; fantasy genre